Efektivitas Penggunaan YouTube Shorts Dalam Penyebaran Informasi (Studi Kasus: Pada Akun Pojok History) - Anfa Tisrin Tantika; M. Rifki Fauzan; Neng Susi Susanti; Sandy Akbar Ramadhana; Tazkia Khairani Ilma; Venda Oktavioni; Rofi’ah Siddiq; Kamalludin Kamalludin (KOLONI, 2024)
The increasingly rapid development of technology allows people to easily access various kinds of information they need, such as information conveyed via YouTube Shorts on the Pojok History account. The Pojok History account is a conventional media that is active in disseminating various kinds of information, both history, Indonesian celebrities, and the most up-to-date information. By using qualitative methods through a case study approach, this research aims to determine the effectiveness of using YouTube Shorts on the Pojok History account in disseminating information. The results of this research show that the use of YouTube Shorts by the Pojok History account is effective in disseminating information. This can be seen in the upload of content entitled "School Children Kept Secret for 40 Years" with a total audience of 6.9 million people, 93 thousand likes, and 3.3 thousand active interactions in the comments column. These results are strengthened by 3 indicators of the effectiveness of information dissemination, namely, Fulfillment of Public Information, Community Participation, Motives for Seeking Information